2022
DOI: 10.1016/j.jbc.2022.101626
|View full text |Cite
|
Sign up to set email alerts
|

A pGpG-specific phosphodiesterase regulates cyclic di-GMP signaling in Vibrio cholerae

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…In the genome of A. butzleri and related species, the nrn and corA genes are fused, suggestive of a close functional relationship. The closest predicted structural matches for B. fragilis NrN are to the pGpG-specific PDE PggH from Vibrio cholerae , which has a role in the turnover of the cyclic nucleotide c-di-GMP 18 and the GdpP PDE from Staphylococcus aureus , which degrades pApA molecules as a component of c-di-AMP signalling systems 19 . Analysis of the DEDD protein suggests structural matches to RNaseT 20 , oligoribonuclease 21 , and the mammalian REXO2 protein, which degrades linear RNA and DNA dinucleotides 22 .…”
Section: Mainmentioning
confidence: 99%
“…In the genome of A. butzleri and related species, the nrn and corA genes are fused, suggestive of a close functional relationship. The closest predicted structural matches for B. fragilis NrN are to the pGpG-specific PDE PggH from Vibrio cholerae , which has a role in the turnover of the cyclic nucleotide c-di-GMP 18 and the GdpP PDE from Staphylococcus aureus , which degrades pApA molecules as a component of c-di-AMP signalling systems 19 . Analysis of the DEDD protein suggests structural matches to RNaseT 20 , oligoribonuclease 21 , and the mammalian REXO2 protein, which degrades linear RNA and DNA dinucleotides 22 .…”
Section: Mainmentioning
confidence: 99%
“…The level of c-di-GMP is controlled by two classes of enzymes, DGCs and PDEs, for the synthesis and degradation of c-di-GMP, respectively ( 41 ). Although PDEs were also up-regulated like DGCs during the bacterial filamentation, PDEs such as PdeF can be inhibited by its catalytic product of c-di-GMP, 5′-pGpG ( 42 ), indicating that their activity is mutually balanced. In our study, c-di-GMP was accumulated during bacterial filamentation and exhibited upregulation.…”
Section: Resultsmentioning
confidence: 99%
“…Nor has it been determined whether different subclasses of NrnA-like proteins may exhibit different substrate preferences and cellular purposes. Interestingly, a recent study demonstrated that a DHH-DHHA1 homolog from Vibrio cholera acts specifically on GG, at the exclusion of other dinucleotides and other short RNA species ( 55 ). This important publication demonstrates proof-of-principle that certain bacteria may have evolved specialized versions of DHH-DHHA1 proteins, and that still more cellular roles for DHH-DHHA1 proteins are likely to await discovery.…”
Section: Resultsmentioning
confidence: 99%